A Post Hoc Power And Effect Size Analysis Of Micro-enterprise Behavior: A Construct Measurement Study Of Rural Asnaf’s Entrepreneurs (rae) Development In Pahang - Muhammad Syahrul Deen; Shofiyyah Moidin; Mohd Izzat Amsyar Mohd Arif; Faezy Adenan; Mohd Saleh Abbas; Albert Feisal Ismail; Khairunneezam Mohd Noor (ResearchTrentz, 2024)
Indexed by Scopus/ERA